Associations of streptococci and fungi amounts in the oral cavity with nutritional and oral health status in institutionalized elders: a cross sectional study - Hanako Sato (BMC, 2021)
Abstract Background Disruption of the indigenous microbiota is likely related to frailty caused by undernutrition. However, the relationship between undernutrition and the oral microbiota, especially normal bacteria, is not obvious. The aim of this study was to elucidate the associations of nutritional and oral health conditions with prevalence of bacteria and fungi in the oral cavity of older individuals. Methods Forty-one institutionalized older individuals with an average age ± standard deviation of 84.6 ± 8.3 years were enrolled as participants. Body mass index (BMI) and oral health assessment tool (OHAT) scores were used to represent nutritional and oral health status. Amounts of total bacteria, streptococci, and fungi in oral specimens collected from the tongue dorsum were determined by quantitative polymerase chain reaction (PCR) assay results. This study followed the STROBE statement for reports of observational studies. Results There was a significant correlation between BMI and streptococcal amount (ρ = 0.526, p < 0.001). The undernutrition group (BMI < 20) showed a significantly lower average number of oral streptococci (p = 0.003). In logistic regression models, streptococcal amount was a significant variable accounting for “not undernutrition” [odds ratio 5.68, 95% confidential interval (CI) 1.64–19.7 (p = 0.06)]. On the other hand, participants with a poor oral health condition (OHAT ≥ 5) harbored significantly higher levels of fungi (p = 0.028). Conclusion Oral streptococci were found to be associated with systemic nutritional condition and oral fungi with oral health condition. Thus, in order to understand the relationship of frailty with the oral microbiota in older individuals, it is necessary to examine oral indigenous bacteria as well as etiological microorganisms.